7 - 6 (1- 7n) = 127
7 - 6 - 42n = 127
1 - 42n = 127
subtract 1 from both sides
- 42n = 126
divide both sides by -42
n = 3
y = 4x + 4
B.
y = 4x − 4
C.
y = −4x + 4
D.
y = −4x − 4
4(6 + 7) = 4 • 6 + x • 7
x =
2. 9/6b^12
3. 27/8b^64
4. 27/8b^27
Answer:
Step-by-step explanation:
I'm going to assume that you accidentally missed a set of parentheses and that the expression is
Raise 2, , and to the third power:
When a variable raised to a power is raised to another power, the exponents are multiplied:
Negative powers are the positive power in the denominator:
Therefore, the answer is the second option.
The simplified form of the given mathematical expression (3/2b^4)^3 is 27/8b^12.
The simplified form of each expression (3/2b^4)^3 is calculated by cubing both the numerator and the denominator. Firstly, 3^3 gives 27, and then (2b^4)^3 simplifies to 8b^12. So the final answer is 27/8b^12. This means, out of the given options, the correct one is Option 1: 27/8b^12.
#SPJ3